Desenvolvimento de itinerário formativo relacionado com a educação física escolar: desafios e perspectivas no Novo Ensino Médio - Machado, Perla Cristina Frangioti (Universidade Federal de São Carlos, 2023)
The law 13.415/2017 changed the so called “Law of Directives and Bases of National Education” (Lei de Diretrizes e Bases da Educação – LDB) and is known as “New High School” (NEM). It promoted changes in its structure and timetable, flexibilized the curriculum, and added the Itinerários Formativos - IF (track of specialization). In 2021, during the Covid-19 pandemic, the public schools of São Paulo State started its implementation. Both the State Department of Education and the schools are not informing clearly about how teachers should work in it, especially regarding/concerning IFs. Therefore, the objective of this research is to analyze the Physical Education teaching processes during the classes of a teacher-researcher under the new guidelines of the IF “Languages and Their Technologies”. The methodology was based on a qualitative analysis, through pedagogical intervention. It was conducted in the first half of 2022, with second year students of the NEM, enrolled in the #SeLigaNaMidia division, component 3: “Journalism and Inclusion in Sports: Practices and Experimentation”. The data collection source was the classroom diaries written by the teacher-researcher. The data analysis was held through the elaboration of categories, as follows: Engagement and impressions of the researcher during the process; Structuring and development of the support material (MAPPA); Strengths and weaknesses of the NEM and the IF. The study pointed out that the NEM presents several problems, from structural to socio-educational, with more weaknesses than strengths. Moreover, the state of São Paulo, when beginning the implementation of the NEM, before the deadline set by the Ministry of Education, generated many doubts and insecurities both among students and teachers, especially regarding the IFs.
Development of track of specialization in the New Hight School: challenges and perspectives
Keywords: Itinerários formativos; Novo ensino médio; Educação física escolar; New High School; School physical education; Track of specialization; CIENCIAS DA SAUDE::EDUCACAO FISICA